Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Variation in the holm oak leaf proteome at different plant developmental stages, between provenances and in response to drought stress. - Jorge, Inmaculada; Navarro, Rafael M; Lenz, Christof; Ariza, David; Jorrín, Jesús (Proteomics, 2006)
Major proteins of the holm oak leaf proteome have been previously identified using a combination of 2-DE, MS analysis and BLAST similarity search (Jorge et al., Proteomics 2005, 5, 222-234). That study, conducted with field samples from mature trees, revealed the existence of a great variability in the 2-DE protein map, with qualitative as well as quantitative changes, both analytical and biological. A similar study has been carried out with 2-year-old seedlings to analyze and study: (i) changes in the 2-DE protein profile at different tree developmental stages; (ii) the 2-DE protein map variability between three different Spanish provenances; and (iii) variations in the 2-DE protein profile in response to drought stress. Although the protein profile of leaves from seedlings and mature trees was fairly similar, the biological variance found was lower in the former. In the present study, new proteins have been identified. At least four different protein spots differentiated Spanish provenances, two of them identified as an ATP synthase alpha chain, and a 2,3-bisphosphoglycerate-independent phosphoglycerate mutase. Fourteen different protein spots were qualitatively variable between well-watered and drought-stressed seedlings, with some of them corresponding to enzymes of carbohydrate and protein metabolism. Data presented indicated the mobilization of storage proteins and carbohydrates, as well as photosynthesis inhibition under drought conditions.
Keywords: Dehydration; Dehydration: metabolism; Disasters; Electrophoresis, Gel, Two-Dimensional; Plant Leaves; Plant Leaves: metabolism; Proteome; Proteome: metabolism; Proteomics; Quercus; Quercus: embryology; Quercus: metabolism; Seedling; Seedling: metabolism

Ultrasound acoustic emissions from bark samples differing in anatomical characteristics - Kikuta, S B (PHYTON-ANNALES REI BOTANICAE, 2003)
This study examines ultrasound acoustic emissions (UAE) from various bark types differing in anatomical characteristics. UAE were detected in dehydrating bark strips from twigs of two conifers (Pinus nigra ARNOLD, Taxus baccata L.), and four woody dicotyledons (Hedera helix L.. Malus sylvestris MILL., Sambuctis nigra L., and Tilia platyphyllos SCOP.) with varying contents of dead mechanical elements in the cortex and in the secondary phloem. If filled with water, non-conducting bark elements (sclereids, fibre-sclereids, secondary phloem fibres and periderm cells) emitted ultrasound during dehydration. Signal production varied between the species and the bark layers studied. Pressure infiltration increased the number of UAE conspicuously. UAE were also registered from infiltrated sections of bottle cork (Quercus suber L.) and infiltrated walnut shells (Juglans regia L.) built of sclereids only and characterised by lignified secondary cell walls. Stems of Sphagnum sp. emitted UAE, probably originating in hyalocysts, dead non-conducting water storage cells in the leaves. Living cells (inner epidermes of bulb scales of Allium cepa L. and collenchyma, strands from the herbaceous stern of Lamium maculatum L.) produced only very few UAE. The results suggest that ultrasound acoustic emissions during dehydration do not only occur in cavitating conducting xylem elements but also in non-conducting, dead cells with thick walls.
Keywords: Bark; cavitation; Dehydration; fibres; infiltration; periderm; sclereids; secondary phloem; ultrasound acoustic emissions

The development of a protocol for the encapsulation-desiccation and in vitro culture of embryonic axes of Quercus suber L-and Q-ilex L. - Gonzalez-Benito, M E; Herradon, E; Martin, C (SILVAE GENETICA, 1999)
Quercus species have seeds recalcitrant against long-term storage. Cryopreservation of embryonic axes could be a feasible way of preserving their genetic diversity. Several cryopreserva- tion protocols are based on desiccation, among them the so- called encapsulation-dehydration. However, it is previously necessary to establish an adequate in vitro culture develop- ment of desiccated axes. Embryonic axes of Q. suber and Q. ilex were aseptically excised, encapsulated in alginate beads, cultur- ed in a sucrose-rich liquid medium, desiccated for different periods in a flow bench and cultured on basal WPM medium. Moisture content of encapsulated axes dropped from 74% to 71% (fresh weigh basis) to 24.5% to 21% after 6 h desiccation, respectively for the two species. Germination decreased to 20% in both species. Germination and shoot elongation of encapsu- lated embryos (non-desiccated or desiccated for 4 h) was stud- ied for both species after culture on WPM medium supplemented with different concentrations of BAP and IBA. Medium with 0.1 mgl-1 BAP resulted in a high percentage of germina- tion and development of shoots in both species
Keywords: aliginate bead; Dehydration; in vitro culture; oak; Quercus; recalcitrant seed